Kepaniteraan peradilan agama - Sy., Musthofa, 1969- (Rawamangun, Jakarta : Kencana, 2005)
On administration of Islamic courts in Indonesia
Includes bibliographical references (p. [259]-262)
Keywords: Islamic courts -- Indonesia; Justice, Administration of (Islamic law) -- Indonesia; Islamic law -- Indonesia